Collaborative learning environments for teacher education - Meirinhos, Manuel (2007)
We present a case study of continuous training of teachers, carried out within a b-learning framework. In this presentation we present and discuss the concepts beyond this approach to teacher education. We also present the structure of the platform used for collaborative work, characterize the participants in this research and illustrate the kind of activities and tasks that were conducted by approximately forty teachers in two continuous professional development courses. Finally, we address a number of reflections emerging from the data collected, including: i) the functionality of the platform; ii) the constrain factors that can affect collaborative learning in such an environment; iii) the changes to the role of the teacher educator; iv) the changes to the role of the teacher learner; v) the development of hew pedagogical inter-relations; vi) the complexity of collaborative learning.